2006
DOI: 10.1242/jcs.03200
|View full text |Cite
|
Sign up to set email alerts
|

CHK1 phosphorylates CDC25B during the cell cycle in the absence of DNA damage

Abstract: CDC25B is one of the three human phosphatases that activate the CDK-cyclin complexes, thereby triggering cell-cycle progression and division. Commitment to early mitotic events depends on the activation of a centrosomal pool of CDK1–cyclin-B1, and CDC25B is thought to be involved in initiating this centrosomal CDK1–cyclin-B1 activity. Centrosome-associated checkpoint kinase 1 (CHK1) has been proposed to contribute to the proper timing of a normal cell division cycle by inhibiting the activation of the centroso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
92
0
9

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 46 publications
5
92
0
9
Order By: Relevance
“…CDC25B phosphatase activity appears to be highly regulated by phosphorylation mechanisms. A number of regulatory kinases that activate or inhibit CDC25B have been identified (Baldin et al, 1997a(Baldin et al, , 2003Bulavin et al, 2002;Theis-Febvre et al, 2003;Dutertre et al, 2004;Cazales et al 2005;Manke et al, 2005;Mirey et al, 2005;Lemaire et al, 2006;Schmitt et al, 2006) (our unpublished data). These phosphorylation events modulate the catalytic activity, the interactions with regulatory partners such as 14-3-3 proteins, the localization and probably also the stability of CDC25B.…”
Section: Introductionmentioning
confidence: 89%
“…CDC25B phosphatase activity appears to be highly regulated by phosphorylation mechanisms. A number of regulatory kinases that activate or inhibit CDC25B have been identified (Baldin et al, 1997a(Baldin et al, , 2003Bulavin et al, 2002;Theis-Febvre et al, 2003;Dutertre et al, 2004;Cazales et al 2005;Manke et al, 2005;Mirey et al, 2005;Lemaire et al, 2006;Schmitt et al, 2006) (our unpublished data). These phosphorylation events modulate the catalytic activity, the interactions with regulatory partners such as 14-3-3 proteins, the localization and probably also the stability of CDC25B.…”
Section: Introductionmentioning
confidence: 89%
“…25 It has been reported that centrosomal Chk1 regulates this activation through its inhibition of the Cdk1-activating Cdc25B phosphatase. [26][27][28] In this model, centrosomal Chk1 localization is regulated by pericentrin, with pericentrin being controlled by Mcph1/BRIT1 (hereafter Mcph1), a centrosomal and nuclear protein that also plays a part in the DNA damage response. 29 However, an alternative model has also been advanced, in which a nuclear Chk1 signal restrains Cdk1 activation, with a different kinase activating the centrosomal Cdk1.…”
Section: Knockdown or Expression Of Dominant-negative Pericentrinmentioning
confidence: 99%
“…One important aspect of centrosome biology is the control of cyclin B1/ CDK1(CDC2) activity for entry into mitosis [55]. Following DNA damage, premature initiation of mitosis is prevented by inhibiting centrosome-associated cyclin B1/ CDK1(CDC2) through CDC25 phosphatase inactivation [56,57]. In HeLa cells treated by VP16, both CDK1(CDC2) and phospho-Bcl-xL(ser49) accumulate in centrosomes during the G2 checkpoint (Supplemental Fig.…”
Section: Bcl-xl(ser49) Phosphorylation and Location During Dna Damagementioning
confidence: 99%